Ligand-activated PPARδ upregulates α-smooth muscle actin expression in human dermal fibroblasts: A potential role for PPARδ in wound healing. Issue 3 (December 2015) - Ham, Sun Ah; Hwang, Jung Seok; Yoo, Taesik; Lee, Won Jin; Paek, Kyung Shin; Oh, Jae-Wook; Park, Chan-Kyu; Kim, Jin-Hoi; Do, Jung Tae; Kim, Jae-Hwan; Seo, Han Geuk
Highlights: Activation of PPARδ induces expression of α-SMA in part through TGF-β signaling. Activation of PPARδ regulated the induction of myofibroblast-related proteins. Activation of PPARδ promoted migration and contraction of the HDFs. Abstract: Background: The phenotypic changes that accompany differentiation of resident fibroblasts into myofibroblasts are important aspects of the wound healing process. Recent studies showed that peroxisome proliferator-activated receptor (PPAR) δ plays a critical role in wound healing. Objective: To determine whether the nuclear receptor PPARδ can modulate the differentiation of human dermal fibroblasts (HDFs) into myofibroblasts. Methods: These studies were undertaken in primary HDFs using Western blot analyses, small interfering (si)RNA-mediated gene silencing, reporter gene assays, chromatin immunoprecipitation (ChIP), migration assays, collagen gel contraction assays, and real-time PCR. Results: Activation of PPARδ by GW501516, a specific ligand of PPARδ, specifically upregulated the myofibroblast marker α-smooth muscle actin (α-SMA) in a time- and concentration-dependent manner. This induction was significantly inhibited by the presence of siRNA against PPARδ, indicating that PPARδ is involved in myofibroblast transdifferentiation of HDFs. Ligand-activated PPARδ increased α-SMA promoter activity in a dual mode by directly binding a direct repeat-1 (DR1) site in the α-SMA promoter, and by inducing expression of transforming growth factor (TGF)-β, whose downstream effector Smad3 interacts with a Smad-binding element (SBE) in another region of the promoter. Mutations in these cis -elements totally abrogated transcriptional activation of the α-SMA gene by the PPARδ ligand; thus both sites represent novel types of PPARδ response elements. GW501516-activated PPARδ also increased the migration and contractile properties of HDFs, as demonstrated by Transwell and collagen lattice contraction assays, respectively. In addition, PPARδ-mediated upregulation of α-SMA was correlated with elevated expression of myofibroblast markers such as collagen I and fibronectin, with a concomitant reduction in expression of the epithelial marker E-cadherin. Conclusion: PPARδ plays pivotal roles in wound healing by promoting fibroblast-to-myofibroblast differentiation via TGF-β/Smad3 signaling.